Encryption method for SCADA security enhancement - Shahzad, Aamir; Musa, Shahrulniza; Irfan, Muhammad; Shah, Asadullah (Asian Network for Scientific Information, 2014)
With the growing demands of Industrial Control Systems (ICS) in all over the world, the industries such as water, electric and gas are using real time infrastructures for communication between filed devices connected within "networks such as using Local Area Network (LAN). Wide Area Networks (WAN)" or/and over internet to fulfill the requiremenets of industrial processing and automation. Supervisory Control and Data Acquisition (SCADA) system is part of ICS. This system is based on real-time processing infrastructure, systems control and design. In existing survey, several mechanisim/solutionms were developed for reliable delivery of data without any attack. Severla techniques were also implemented " such as using secure socket layer/transport layer security (SSL/TLS), secure shell (SSH) and Internet Protocol Security (IPSec)" for securing data across internet and overcoming the attacks and security because these are based on TCP/IP protocol for communication and on cryptography algorithms for the purpose of security. Based on detail SCADA security analysis, the cryptography techniques have been adopted to enhance the security of these critical systems. The proposed security solutions takes novel approach to implement the best security performance cryptography algorithms included AES, RSA and SHA-2, as a security layer within distributed network protocol (DNP3) stack. This novel approach successfully enhanced the security of DNP3 protocol as a part of SCADA system while comparing with end-to-end security implementations.